2019
DOI: 10.7150/jca.27160
|View full text |Cite
|
Sign up to set email alerts
|

5'-Methylthioadenosine and Cancer: old molecules, new understanding

Abstract: While the metabolic changes in cancer tissues were first observed by Warburg Otto almost a century ago, altered metabolism has recently returned as a focus of cancer research. 5'-Methylthioadenosine (MTA) is a naturally occurring sulfur-containing nucleoside found in numerous species. While MTA was first isolated several decades ago, a lack of sensitive and specific analytical methodologies designed for its direct quantification has hampered the study of its physiological and pathophysiological features. Many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 84 publications
0
30
0
Order By: Relevance
“…In high methionine condition there was also an increase of two direct methionine derivatives, the regulatory metabolite methylthioadenosine (MTA) and the toxic compound methionine sulfoxide ( Figure 4 D). Remarkably, the MTA level negatively correlates with growth potential in the liver [ 36 , 37 ]. In fact, it has been reported that MTA decreases after partial hepatectomy, when the replicative response of hepatocytes is higher [ 38 ], and MTA administration in vitro reduces liver cell growth [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In high methionine condition there was also an increase of two direct methionine derivatives, the regulatory metabolite methylthioadenosine (MTA) and the toxic compound methionine sulfoxide ( Figure 4 D). Remarkably, the MTA level negatively correlates with growth potential in the liver [ 36 , 37 ]. In fact, it has been reported that MTA decreases after partial hepatectomy, when the replicative response of hepatocytes is higher [ 38 ], and MTA administration in vitro reduces liver cell growth [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it has been reported that MTA decreases after partial hepatectomy, when the replicative response of hepatocytes is higher [ 38 ], and MTA administration in vitro reduces liver cell growth [ 39 ]. Furthermore, MTA inhibits the synthesis of polyamines [ 36 ], whose level is correlated with proliferation and which were indeed decreased in high methionine condition (see spermidine and putrescine, Figure 4 E). On the contrary, the MTA derivatives adenine and adenosine increased in high methionine condition ( Figure 4 E).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5). Methylthioadenosine, a product of the polyamine metabolism that affects various metabolic and cellular processes including cell growth [43,44], was also lower in bodies of n per 01 relative to n WT CS (Suppl. Figure 6e).…”
Section: Per 01 Affects the Level Of Tryptophan But Not Other Amino mentioning
confidence: 99%
“…The effects of MTA are accompanied by inhibition of circulating tumor necrosis factor-α (TNF-α), inducible nitric oxide synthase (iNOS) expression, and stimulation of IL-10 synthesis. MTA can inhibit the transcriptional activation of iNOS by proinflammatory cytokines in liver cells, inhibit the induction of COX2 in raw264.7 cells, inhibit p38 mitogen-activated protein kinase (MAPK), c-jun phosphorylation, inhibitor kappa B alpha (IB) degradation, and nuclear factor B (NFĸB) activation, all of which are signaling pathways related to the production of inflammatory mediators ( Eloranta et al., 1982 ; Li Y. et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%